PEMANFAATAN TEKNOLOGI OTOMATIS PADA MESIN PENGGULINGAN BABI - Widhiada, I Wayan (Buletin Udayana Mengabdi; Vol 19 No 3 (2020): Buletin Udayana Mengabdi, 2020)
In general, the Balinese who have a business selling pork roll still use technology manually where one person will spin the wand used to roast the pig and another fan of the pork roll until it gets a good grill. The time needed to produce one pig roll that is ready to be served on average takes around 3 hours. With the limitations of the technology manually, the servants, as well as researchers, have designed technology based on the automation of roasted pork roasting machines. The Brushed DC motor with a maximum rotation of 2750 rpm will be used to rotate the device with a variety of rotation of high, medium, and low speeds. In the design of this machine, there are 4 bolsters that can be roasted at the same time in the furnace. The distribution of heating in the combustion chamber will also be controlled automatically so that it can increase roast production in a faster time than before and a better quality of pork roll. With the application of this automatic roasting machine, it is expected that it can help restaurant entrepreneurs increase production, efficiently so as to increase profits.